Indicators of rearrest among male court mandated substance use treatment patients. Issue 1 (14th March 2016) - Kopak, Albert M.; Proctor, Steven L.; Hoffmann, Norman G.
Abstract : Purpose: – Effective substance use treatment is a viable way to reduce criminal justice contact among drug-involved offenders, but there is still a lot to learn about which indicators have the greatest impact on treatment outcomes. The purpose of this paper is to determine which clinical indicators influenced the likelihood of rearrest among male drug-involved offenders. Design/methodology/approach: – This prospective longitudinal study examined indicators of 12-month post-treatment rearrest for male criminal justice-involved substance use treatment patients. Multinomial logistic regression results drawn from a sample of 1, 531 adult male patients who were mandated to substance use treatment indicated that there were different factors related to the likelihood of one as well as multiple post-treatment arrests. Findings: – Demographic risk factors, such as age and unemployment, were associated with significant increases in the probability of experiencing an arrest within 12-months of treatment discharge. Substance use relapse was also a significant indicator of the likelihood of rearrest and contributed to an increase in the odds of one post-treatment rearrest as well as multiple rearrests. A drug dependence diagnosis, relative to a diagnosis for alcohol dependence, was associated with an increased likelihood of rearrest. Participation in outpatient treatment was associated with a lower likelihood of rearrest. Practical implications: – These findings emphasize the need for treatment providers to concentrate heavily on demographic risk reduction to minimize the chance that male patients are rearrested after treatment. Relapse prevention, on the other hand, is critical in the effort to minimize the number of post-treatment rearrests in this population. Originality/value: – The results from this study provide evidence to empirically support the refinement of substance treatment programs for male patients involved in the criminal justice system.